In vitro activity of cefepime/zidebactam (WCK 5222) against Gram-negative bacteria. (3rd February 2017) - Livermore, David M.; Mushtaq, Shazad; Warner, Marina; Vickers, Anna; Woodford, Neil
Abstract : Objectives: Diazabicyclooctanes (DBOs) inhibit class A, class C and some class D β-lactamases. A few also bind PBP2, conferring direct antibacterial activity and a β-lactamase-independent 'enhancer' effect, potentiating β-lactams targeting PBP3. We tested a novel DBO, zidebactam, combined with cefepime. Methods: CLSI agar dilution MICs were determined with cefepime/zidebactam in a chequerboard format. Bactericidal activity was also measured. Results: Zidebactam MICs were ≤2 mg/L (mostly 0.12–0.5 mg/L) for most Escherichia coli, Klebsiella, Citrobacter and Enterobacter spp., but were >32 mg/L for Proteeae, most Serratia and a few E. coli, Klebsiella and Enterobacter/Citrobacter . The antibacterial activity of zidebactam dominated chequerboard studies for Enterobacteriaceae, but potentiation of cefepime was apparent for zidebactam-resistant isolates with class A and C enzymes, illustrating β-lactamase inhibition. Overall, cefepime/zidebactam inhibited almost all Enterobacteriaceae with AmpC, ESBL, K1, KPC and OXA-48-like β-lactamases at 1 + 1 mg/L and also 29 of 35 isolates with metallo-carbapenemases, including several resistant to zidebactam alone. Zidebactam MICs for 36 of 50 Pseudomonas aeruginosa were 4–16 mg/L, and the majority of AmpC, metallo-β-lactamase-producing and cystic fibrosis isolates were susceptible to cefepime/zidebactam at 8 + 8 mg/L. Zidebactam MICs for Acinetobacter baumannii and Stenotrophomonas maltophilia were >32 mg/L; potentiation of cefepime was frequent for S. maltophilia, but minimal for A. baumannii . Kill curve results largely supported MICs. Conclusions: Zidebactam represents a second triple-action DBO following RG6080, with lower MICs for Enterobacteriaceae and P. aeruginosa . Clinical evaluation of cefepime/zidebactam must critically evaluate the reliance that can be placed on this direct antibacterial activity and on the enhancer effect as well as β-lactamase inhibition.